Evaluating the Efficacy and Safety of Baricitinib in Reducing COVID-19 Mortality: A Comprehensive Review of Clinical Evidence and Pharmacological Strategies - Kwaśniewska, Paulina Klaudia; Graczyk, Patryk; Wilewska, Anna; Borowiec, Kinga; Borowiec, Agnieszka; Biernikiewicz, Julia; Alabrudziński, Konstanty; Biernikiewicz, Milena; Pomirski, Bartosz; Pomirska, Agata (Journal of Education, Health and Sport, 2024)
Introduction: COVID-19 manifests with symptoms ranging from mild to severe, including respiratory and cardiovascular complications. Severe cases are often marked by a cytokine storm, causing pulmonary damage and multi-organ dysfunction. Current treatments lack a specific antiviral, though several pharmacological options, including immunomodulatory and antiviral drugs, are under investigation. Purpose: The purpose of this article is to provide an evaluation of the efficacy and safety of baricitinib, a JAK inhibitor, combined with standard care for hospitalized adults with COVID-19. By reviewing recent literature, it aims to assess baricitinib’s effectiveness in improving patient outcomes. Material and methods: A systematic review of clinical trials and case studies was conducted to analyze baricitinib’s impact on COVID-19 mortality. Data includes treatment-emergent adverse events and patient outcomes in moderate to severe cases. Discussion: Baricitinib has demonstrated potential in managing hyperinflammation in severe COVID-19 by inhibiting multiple proinflammatory cytokines and enhancing immune response. Clinical trials show that baricitinib, particularly in combination with corticosteroids, reduces mortality and serious infections compared to standard care alone. Due to potential adverse events, continuous monitoring of hematological and lipid levels is essential. These findings highlight baricitinib’s dual role as an immunomodulatory and antiviral agent, suggesting its importance in treating severe COVID-19. Future research should focus on optimizing treatment regimens and further exploring the long-term implications of baricitinib therapy.